DIGITAL TRANSFORMATION AND ADVERTISING STRATEGIES ON SPANISH RADIO: A COMPARATIVE ANALYSIS OF CADENA SER, COPE, AND ONDA CERO - López, Concepción Gómez (Seven Editora, 2025)
This study examines the evolution of digital and advertising strategies of Cadena SER, Onda Cero and COPE, audience leaders according to the EGM (2024). Using a qualitative-descriptive method based on content analysis (Krippendorff, 1990; Bardin, 1986), we compare the structure, user interactivity and advertising strategies of their websites. Key aspects such as accessibility, live radio, on-demand content, digital native audio, interactivity and content personalisation are examined. The findings reveal notable differences in organisation, engagement and personalisation. The study concludes that Spanish online radio is migrating to a multiplatform model, facilitating audience expansion and diversification of the advertising business, although challenges remain in personalisation and digital advertising integration.DOI: https://doi.org/10.56238/sevened2025.036-097